A brief review on phytochemistry and pharmacology of Taxus baccata L. (2022) - Sharma, Ashish; Sharma, Ajay; Thakur, Sakshi; Mutreja, Vishal; Bhardwaj, Garima
Highlights: Taxus baccata L. is an ethnomedicinal plants commonly known as Yew tree. Traditionally, it is widely used to treat variety of ailments. Taxol, a potent anticancer drug is present in the small amount in shoots of Yew. It also known to show wide range of pharmacological activities. All the parts of Yew tree are rich source of various bioactive alkaloids and flavonoids. Abstract: Mother Nature is full of surprises, hiding several gems beneath its heart in the form of forests, mountains, rivers, etc. One of the treasures that human got as a gift are the forests which value more than anything presents on this earth in terms of its significance. Still, humans are not realizing the full potential of trees and driving deforestation with supersonic speed (see the example of Amazon forests in Brazil). One of such trees which might face extinction soon is Taxus baccata L. Also called Yew, the tree is the toolbox for various kinds of diseases since ancient times. It is important for the common people and the scientific community to understand the importance of the chemical constituents present in it in the form of alkaloids, flavonoids, and essential oils. Here in this review, we will shed the light on the natural products present in Yew and their applications, side effects, and medicinal properties. Afterward, we will discuss the ADME (absorption, distribution, metabolism, and excretion) of Yew constituents, as most of the part of the tree is toxic for human consumption. This review will give insight into the T. baccata species and will be helpful for the medicinal chemists to design new molecules for various cancers, fungal and microbial infections, and asthma.